2013
DOI: 10.1016/j.jhydrol.2013.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Surface water connectivity dynamics of a large scale extreme flood

Abstract: During flood inundation, river water passes from the main channel into the floodplain through floodplain channels and diffusive overbank flow. This flood water is then distributed within the floodplain depending upon internal connections, barriers and storage, and finally returns back to the river through drainage connections. This surface water connectivity can be complex and is important to many aspects of floodplain functioning, including ecology, sediment movement and flood risk. However, there is currentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 42 publications
3
47
1
Order By: Relevance
“…We examined the flow snapshots for this period and found that overland flow is gradually drained out of the topography, but the maximum lag distance of the connected flow pathways remains at approximately half of the maximum lag distance of the watershed, that is, connected flow can still extend across half of the watershed scale (regardless of flows in stream channel or floodplain). This finding is consistent with other studies that have described how, during recession limbs, flow slowly spills out of low laying areas (depressions) but remains connected within the scale of these areas (e.g., Trigg, Michaelides, Neal, & Bates, 2013) 3.3 | Role of depressions on overland flow connectivity changes across spatial scales-direction…”
Section: Role Of Depressions On Overland Flow Connectivity Changes supporting
confidence: 91%
“…We examined the flow snapshots for this period and found that overland flow is gradually drained out of the topography, but the maximum lag distance of the connected flow pathways remains at approximately half of the maximum lag distance of the watershed, that is, connected flow can still extend across half of the watershed scale (regardless of flows in stream channel or floodplain). This finding is consistent with other studies that have described how, during recession limbs, flow slowly spills out of low laying areas (depressions) but remains connected within the scale of these areas (e.g., Trigg, Michaelides, Neal, & Bates, 2013) 3.3 | Role of depressions on overland flow connectivity changes across spatial scales-direction…”
Section: Role Of Depressions On Overland Flow Connectivity Changes supporting
confidence: 91%
“…There has been a recent tendency toward merging the concept of hyporheic flow, which occurs at all times [ Buffington and Tonina , ], with classical concepts of bank storage [ Pinder and Sauer , ; Sophocleous , ] and overbank flow [ Mertes , ; Tockner et al ., ; Trigg et al ., ] that are caused by fluctuating water levels during spates and floods. The effect that river flooding has on hyporheic flow through bar and riffle features has been widely investigated [ Gariglio et al ., ; Nowinski et al ., ; Shope et al ., ; Francis et al ., ; Käser et al ., ; Wondzell and Swanson , ; Harvey et al ., ].…”
Section: Mechanisms Of Exchange At the Surface‐subsurface Interfacementioning
confidence: 99%
“…Remote sensing methods have the ability to acquire information on inundation and surface water connectivity over large areas relatively cheaply (Bates, 2004;Chen et al, 2013;Trigg et al, 2013;Dzubakova et al, 2015). However, affordable remotely sensed products have limited application for evaluating wetland connectivity.…”
Section: Introductionmentioning
confidence: 99%